Dosa Yang Mendatagkan Maut Dan Tidak Mendatangkan Maut 1 Yohanes 5:16-17 Serta Pengaruhnya Bagi Orang Kristen Masa Kini - Hendrik Irwansyah Zebua; Abad Jaya Zega (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The interpretation of 1 John 5:16, 17, which distinguishes between sin leading to death and sin not leading to death, remains a topic of debate among Bible scholars. Diverse viewpoints arise from theological interpretations and biblical studies. Further dialogue is necessary to gain a deeper understanding of this verse. Employing exegetical methods, the author endeavors to elucidate the concept of mortal sin and non-lethal sin. The research centers on scrutinizing sin in 1 John, particularly in verses 2:1 and 3:8, and comparing it with the context of verses 5:16, 17. It considers factors such as faith in Jesus as the Mediator and situations involving conscious sin or continuous transgression against God's law, both of which lead to death. A sin that doesn't lead to death pertains to a believer who, during their life's journey, may sin but subsequently confesses to God. In such cases, God forgives, preventing eternal death.